Pengaruh Model Pembelajaran Discovery Learning Berbantuan Flipped Classroom terhadap Hasil Belajar di SMAN 1 Perhentian Raja - Audrel Abelita Putri; Gimin Gimin; Hariyanti Hariyanti; Sri Erlinda (Departement of Mathematics Education, 2023)
The purpose of this research is to find out and analyze whether there is an effect of the flipped classroom-assisted discovery learning model on PPKn learning outcomes at SMAN 1 Perhantian Raja. This research method is quantitative, data analysis was carried out on research samples through a statistical approach to determine the effect of the flipped classroom-assisted discovery learning model on Civics learning outcomes of SMAN 1 Perhentian Raja students. The data collection instrument used in, learning outcomes in the form of pretest and posttest. The population in this study were students of SMAN 1 Perhentian Raja class XI IPA 1. The purposive sampling technique was used to determine the sample with the consideration that learning outcomes were cognitive. Learning outcomes experienced an increase in average and classical. The average score obtained at the pretest was 61.88 and the posttest was 81.23 while the classical completeness at the posttest was 17.64 and the pretest was 88.23. And the results of the calculation of the hypothesis test using the t-test formula for paired/related samples obtained the value seen by the Sig value. (2-tailed) = 0.000 with a level of 5% or 0.05. So 0.05 > 0.00 for a significant level of 5%. Based on the criteria for testing the hypothesis using paired sample t-tests, that is, if Ha is accepted or Ho is rejected, it can be said that there is a significant difference. This shows that Civics learning using the flipped classroom-assisted discovery learning method has on student learning outcomes in Civics class XI IPA 1 students at SMAN 1 Perhentian Raja.